Penerapan Automatic Particle Counter untuk Pemantauan Kondisi Oli Hidrolik - Erdani, Yuliadi; Gumadi, Riki Adiwijaya (Jurnal Otomasi Kontrol dan Instrumentasi, 2024)
High solid particle contamination in hydraulic oil can cause abnormal damage to hydraulic system components. Monitoring the hydraulic oil solid particle contamination level is necessary to ensure it is always within permissible limits. Monitoring of solid particle contamination in hydraulic oil is still done manually by taking an oil sample and then measuring the level of solid particle contamination in the oil sample. This method still relies on human power. Therefore, there is still a possibility that oil conditions are not monitored due to human negligence. This research aims to design a system that automatically samples hydraulic oil and measures solid particle contamination. The level of solid particles in the hydraulic oil is measured by the Automatic Particle Counter (APC) sensor, and then the data is sent to the microcontroller. The microcontroller will process this data and provide information regarding the level of solid particles in the hydraulic oil in real-time. This research produces a system that automatically monitors and produces ISO Cleanliness Code values and a warning system when solid particle levels exceed specified limits. Therefore, this tool can help users monitor hydraulic oil conditions more easily.